(untitled) (Ghana Journal of Science, Technology and Development, 2025)
Persistent variations in land use along with land cover in Densu River basin over time, have contributed significantly to climatic situations in the basin. This phenomenon has impacted the hydrological parameters of the catchment. Therefore, it is essential to analyse the repercussions of dynamic changes in land use, anthropogenic activities and climate variability on hydrologic regimes of the Densu River basin. The dynamic land-use-change modeller, Soil Water Assessment Tool (SWAT) besides Geographic Information System were applied in this research. The land use change from 1986 to 2005 recorded a decline in dense forest cover from 69% to around 26% whilst open forest increased from around 16% to approximately 52%. The results depicted those major hydrological processes in the Densu basin were significantly influenced by curve-number (CN2), groundwater-delay-time (GW_Delay) and baseflow-alpha-factor (Alpha_BF). Based on recommended performance statistics for model timesteps, Nash-Sutcliffe-Efficiency results for calibration and validation of the simulations were above 0.80 and classified as good. The PBIAS results were classified as good. The spatial dispersion of the basin’s evapotranspiration and groundwater recharge zones for the basin were identified. This research provides a foundation for developing strategies for monitoring groundwater recharge zones and other hydrological processes in river basins.